FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN EKONOMI PRODUKTIF RUMAH TANGGA MISKIN DI KELURAHAN SUBAMIA KECAMATAN TABANAN - Rantau, Ketut; Yudhari, Dewa Ayu (JURNAL MANAJEMEN AGRIBISNIS, 2018)
This study aims to determine the effect of age factors, working hours, and the number of dependents simultaneously and partially to the productive economic income of poor households in Subamia Sub-District Tabanan. This research was conducted for three months, starting from August until October of 2017. This research use saturated samplingmethod, that is sample determination technique if all members of the population are used as sample (Sugiyono, 2008: 88), then the number of research samples according to the number a population of 104 poor households. The data obtained were analyzed by multiple linear regression analysis, and test of significance of regression coefficient, so as to give an accurate picture about factors that could influence the productive economic income of poor household head in Subamia sub-district of Tabanan sub-district. From the research result it can be concluded that age factor, hours of work, and the number of dependents simultaneously and partially significantly affect the productive income of poor households in Subamia village, Tabanan sub-district, with 5% siginical level and with R² 0.781, which means 78.1 percent of variation the decrease in earning income of poor household head is influenced by the variable of age factor, working hours, and the number of dependents, the rest of 21.9 percent is influenced by other factors not included in the research variables.